2001
DOI: 10.1007/s004420000560
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity in recruitment of larval trematodes to snail intermediate hosts

Abstract: Spatial variation in parasitism is commonly observed in intermediate host populations. However, the factors that determine the causes of this variation remain unclear. Increasing evidence has suggested that spatial heterogeneity in parasitism among intermediate hosts may result from variation in recruitment processes initiated by definitive hosts. I studied the perching and habitat use patterns of wading birds, the definitive hosts in this system, and its consequences for the recruitment of parasites in snail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 42 publications
(72 reference statements)
5
106
1
5
Order By: Relevance
“…We found a significant negative correlation between density of snails and the proportion of snails infected by trematode parasites, suggesting that parasites may determine, at least in part, the current population density in our study system. From other studies it is known that the prevalence of infection in snails is largely determined by the presence and movements of infected definitive hosts (mammals and birds; see , Sousa 1990;Jokela and Lively 1995;Esch et al 2001;Smith 2001), and is thus potentially subject to a high degree of spatial and temporal variation (Brown et al 1988;Sousa 1990;Esch et al 2001). Perhaps, then, variation in the prevalence of trematode infection causes fluctuations in population size, decreasing long-term effective size and increasing the amount of drift load.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant negative correlation between density of snails and the proportion of snails infected by trematode parasites, suggesting that parasites may determine, at least in part, the current population density in our study system. From other studies it is known that the prevalence of infection in snails is largely determined by the presence and movements of infected definitive hosts (mammals and birds; see , Sousa 1990;Jokela and Lively 1995;Esch et al 2001;Smith 2001), and is thus potentially subject to a high degree of spatial and temporal variation (Brown et al 1988;Sousa 1990;Esch et al 2001). Perhaps, then, variation in the prevalence of trematode infection causes fluctuations in population size, decreasing long-term effective size and increasing the amount of drift load.…”
Section: Discussionmentioning
confidence: 99%
“…However, defining local diversity will depend on the home-range of different hosts and vectors and the spatial scale at which they interact (landscape epidemiology) (see Ostfeld et al, 2005). For example, the movement of short-lived trematode miracidia is often extremely local, frequently leading to significant spatial heterogeneity in snail infections, even within a single wetland ecosystem (Smith, 2001). In contrast, tick vectors are comparatively long lived and can travel widely with their vertebrate hosts, effectively increasing the spatial scale of transmission.…”
Section: How Does the Relationship Between Diversity And Disease Varymentioning
confidence: 99%
“…Because the diversity and abundance of these additional hosts correlates with species richness and prevalence of trematodes infecting horn snails at small spatial scales (Smith 2001, Hechinger and Lafferty 2005, Hechinger et al 2007), these final and second intermediate hosts might drive some of the observed diversity patterns. However, both bird and second intermediate host richness are likely greater in the tropics, considering general diversity patterns in the ocean (Hillebrand 2004, Roy andWitman 2009).…”
Section: Possible Explanations For the Reversed Ldgsmentioning
confidence: 99%